Efektivitas Penerapan Perilaku Disiplin terhadap Kinerja Pegawai (Studi Kasus pada UIN Sultan Aji Muhammad Idris Samarinda) - Lestari, Yenni Tria (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2022)
Employee discipline is something that really needs to be upheld so that every employee performs well. Likewise, the discipline of ASN employees is also very important to be carried out in accordance with applicable laws. As this study aims to see the effectiveness of the application of disciplinary behaviour of ASN employees on performance at UINSI Samarinda. This type of research is qualitative with a juridical-normative approach. Extracting data in the form of interviews, observation, and documentation. The results of this study indicate that the performance of ASN employees at UINSI has carried out their obligations in accordance with the mandate of the applicable laws and regulations. The effectiveness of the application of discipline for ASN employees in accordance with applicable law and running effectively.